Unrevealing the enigma of an oral lump: a comprehensive study of unique histopathological features of giant cell fibroma treated with 940 nm diode laser - Takalkar, Mansi; Karvekar, Shruti; Pattar, Vilas; Hugar, Shweta; Shaik, Shahanaz; Kumar, Roohu Rajinder (International Journal Of Community Medicine And Public Health, 2024)
Connective tissue of oral cavity when exposed to several aetiologies develops a wide range of lesions with particular characteristics. Giant cell fibroma (GCF) has overlapping clinical features with other hyperplastic lesions therefore require a detail histopathological examination. A 58 years old patient with soft tissue overgrowth on left buccal mucosa was excised with 940 nm soft tissue diode laser (Biolase) and the excised tissue was sent for biopsy. Histopathological examination gave a differential diagnosis of GCF, the excision was done using 940 nm laser with uneventful procedure. Patient was recalled after 15 days for follow up, the healing was completed without scar tissue formation. Detailed knowledge about the particular characters of a pathology will help in accurate diagnosis and treatment planning. A clinically normal case may have a significant hidden features which should be followed and searched.